MANAJEMEN BEBAN KOGNITIF GURU DALAM PENGEMBANGAN KURIKULUM MERDEKA: SEBUAH STRATEGI REDISTRIBUSI TUGAS MELALUI KURIKULUM KOLABORATIF ANTAR-SEKOLAH - Dedi Mugni Permadi; Ismael Ismael; Pamuji Pamuji; Nursilawati Nursilawati; Feryna Feryna (Jurnal Manajemen Pendidikan, 2026)
The implementation of the Independent Curriculum has significantly increased teachers' cognitive load due to new demands such as developing teaching modules, diagnostic assessments, P5 projects, as well as differentiated and competency-based learning. This unnecessary extraneous load leads to mental fatigue, decreased quality of curriculum development, and resistance to change. This study aims to formulate a model for managing teachers' cognitive load through a task redistribution strategy based on inter-school collaborative curriculum. The method used is library research with a qualitative approach, employing documentation techniques and content analysis of various sources such as books, journals, articles, and relevant policy documents. The results show that the proposed model is grounded in distributed cognition theory and the concept of professional learning communities expanded across schools. This model applies four principles: task distribution based on competence, standardization of collaborative artifacts, regular reflection cycles, and technological support. The implementation stages include initiation, mapping, joint development, validation, independent implementation, as well as reflection and revision. The implications of this study include policy recommendations for education offices to form curriculum collaboration clusters, for school principals to facilitate teacher participation, and for teachers to shift their paradigm from individual work to collaborative work.